Fampridine: Long-term benefits in walking in multiple sclerosis. (28th February 2017) - Bennett, Susan E.
Abstract : Multiple sclerosis (MS) is a chronic demyelinating disease that affects the brain and spinal cord, causing a disturbance of nerve conduction that impairs function. In a survey conducted in 2008, 1 individuals with MS rated walking as their most important function. Rehabilitation interventions are successful in increasing strength and balance in people with MS, resulting in improved walking. Pharmacologic agents are available that can improve walking for many people with MS (PwMS). Dalfampridine is a broad-spectrum potassium channel blocker that enhances action potential conduction across demyelinated axons. The benefits of dalfampridine have been demonstrated in 2 clinical trials, showing improved walking in PwMS, as demonstrated by improved walking speed. 2, 3 The long-term efficacy of dalfampridine had not been investigated.